2011
DOI: 10.1007/s10765-011-1022-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Co–C and Pd–C Eutectic-Point Cells for Thermocouple Calibration Between LNE-Cnam and NMIJ

Abstract: Evaluation of the melting temperatures of two Co-C and two Pd-C eutectic-point cells were performed using three Pt/Pd thermocouples constructed at LNE-Cnam and NMIJ. During the comparison of cells, Pt/Pd thermocouples were evaluated at the Ag fixed point, at which their drifts and inhomogeneity represented differences within 0.03 • C and 0.14 • C, respectively. One Co-C cell and one Pd-C cell were designed and constructed at LNE-Cnam, while one Co-C cell and one Pd-C cell were designed and constructed at NMIJ.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The temperature differences between the melting temperatures of Cell SP−L and Cell NMIJ−L were found to be 0.05 • C and 0.04 • C using the Pt/Pd thermocouples and the Co-C cell, respectively, as transfers. The expanded uncertainty (k = 2) was from 0.04 • C to 0.05 • C. These temperature differences were small enough, within 0.1 • C, and agree with the results reported in previous research [3,4] as described in Sect. 1.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The temperature differences between the melting temperatures of Cell SP−L and Cell NMIJ−L were found to be 0.05 • C and 0.04 • C using the Pt/Pd thermocouples and the Co-C cell, respectively, as transfers. The expanded uncertainty (k = 2) was from 0.04 • C to 0.05 • C. These temperature differences were small enough, within 0.1 • C, and agree with the results reported in previous research [3,4] as described in Sect. 1.…”
Section: Discussionsupporting
confidence: 92%
“…As recently reported, several laboratories performed and reported a comparison for thermocouples at the melting temperature of Co-C cells [2][3][4], and it was found that the difference of the measured melting temperature of the Co-C cells was within 0.1 • C in spite of slightly different cell designs and different material sources. On the other hand, since the Co-C eutectic point is not a defined fixed point on the International Temperature Scale of 1990 (ITS-90) [5], the melting temperature of the Co-C cell for thermocouple calibration needs to be determined by using a calibrated radiation thermometer.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Above 1000 °C, LNE-Cnam have a series of high temperature fixed-points (HTFPs) up to a temperature of 1500 °C suitable for thermocouple calibration, as well as a number of HTFPs up to a temperature of 1953 °C which are used for radiation thermometry but can be adapted for thermocouple calibration [19,[33][34][35][36][37][38]. However, due to technical problems with the furnace used for realizing these fixed points, the LNE-Cnam measurements in this article were restricted to the wire bridge calibrations using Pd and Pt points, and the freezing point of silver using a conventional tube furnace.…”
Section: Lne-cnam Facilitiesmentioning
confidence: 99%